2007
DOI: 10.1002/ibd.3780050411
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative recurrence of Crohn's disease: Pathophysiology and prevention

Abstract: Postoperative recurrence of Crohn's disease is often inevitable. Certain risk factors such as smoking, young age, and a perforating disease behavior have been identified. Patients running an enhanced risk should be treated with mesalamine or, with higher success rates, with azathioprine. An endoscopic evaluation of the neoterminal ileum 6 to 12 months after surgery provides relevant information predicting the further clinical course and can be used as a guide to adjust medical therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…In addition to altering the neural modulation of motility in Crohn's disease, immune cells may influence the natural history of the disease. Recent preliminary reports by D'Haens et al (15,16) showed a positive correlation between the perineural infiltration by immunocytes in the myenteric plexus of surgically resected Crohn's disease specimens and the subsequent development of disease recurrence postoperatively. Taken together, these observations indicate that while the focus of inflammation in Crohn's disease may be in the mucosa, the presence of T cells in the muscularis externa may be important not only in symptom generation by altering gut physiology, but also in determining the clinical course of the disease.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition to altering the neural modulation of motility in Crohn's disease, immune cells may influence the natural history of the disease. Recent preliminary reports by D'Haens et al (15,16) showed a positive correlation between the perineural infiltration by immunocytes in the myenteric plexus of surgically resected Crohn's disease specimens and the subsequent development of disease recurrence postoperatively. Taken together, these observations indicate that while the focus of inflammation in Crohn's disease may be in the mucosa, the presence of T cells in the muscularis externa may be important not only in symptom generation by altering gut physiology, but also in determining the clinical course of the disease.…”
Section: Discussionmentioning
confidence: 95%
“…Traditionally, studies on the pathogenesis and pathophysiology of Crohn's disease have focused on the mucosal compartment, despite the fact that serious complications such as the development of strictures and fistulae emphasize the transmural nature of the inflammatory process. Recent evidence suggests that the presence of T cells in the deeper neuromuscular layers of the gut may more accurately predict postoperative recurrence of the disease than mucosal changes (15,16). Although medical treatment of Crohn's disease may improve mucosal lesions, it seldom prevents the development of strictures, and this may reflect differences in immune activity between the mucosal and subserosal compartments of the gut.…”
mentioning
confidence: 99%
“…An attempt to classify Crohn's disease on the basis of inflammatory patterns [172] has been compromised by the tendency towards the development of stenoses over time [173]. In contrast to the potential of curing ulcerative colitis with a colectomy, Crohn's disease is usually not cured by surgery; intestinal resection and anastomosis is almost inevitably followed by recurrence of the disease involving the anastomotic site and proximal intestine [174].…”
Section: Crohn's Diseasementioning
confidence: 99%
“…After ileocolectomy with end ileostomy or fecal diverting ileostomy for refractory CD, management should include identification of high-risk patients and careful endoscopic evaluation for monitoring for CD recurrence. Endoscopic evaluation of the neoterminal ileum is recommended 6-12 months after surgery, given the fact that endoscopic recurrence typically precedes relapse of symptoms [10][11][12].…”
Section: Discussionmentioning
confidence: 99%